Cerebellar degeneration-related protein 1 expression in fibroblasts of patients affected by down syndrome. Issue 1 (1st January 2020) - Salemi, Michele; Rappazzo, Giancarlo; Ridolfo, Federico; Salluzzo, Maria Grazia; Cannarella, Rossella; Castiglione, Roberto; Caniglia, Salvatore; Tirolo, Cataldo; Calogero, Aldo E.; Romano, Corrado
Abstract : Down syndrome (DS) is the most common genetic cause of intellectual disability, resulting from lack of disjunction of sister chromatids of human chromosome 21 or not partial disjunction of chromosome 21 (Hsa21), usually during maternal meiosis. The expression of genes in chromosome 21 is very complex and many other genes in other chromosomes can play a role in DS. The protein encoded by the Cerebellar degeneration-related autoantigen 1 ( CDR1 ) gene has been identified in patients with paraneoplastic cerebellar degeneration. Transcriptome studies show CDR1 expression in tumor cell lines and leukocytes of normal subjects and patients with Alzheimer's disease. We investigated CDR1 expression in cultured fibroblasts of DS patients compared with normal subjects. The study of CDR1 mRNA was performed with qRT-PCR. Immunofluorescence and Western blot were used for the analysis of the CDR1 protein. Our data show that both CDR1 mRNA and protein are expressed in human fibroblasts and that the CDR1 gene is down-regulated in DS fibroblasts compared to controls. These data suggest a role for CDR1 in DS phenotype.